COLLABORATIVE GOVERNANCE DALAM UPAYA PEMBERANTASAN ROKOK ILEGAL DI PROVINSI BALI - Daniel Sonatha Sinaga; Sofjan Aripin; Andi Wijaya (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Comprehensive eradication of illicit cigarettes in Indonesia is difficult because their circulation is done secretly. Surveys show that the circulation of illicit cigarettes in Bali increased by 492.13% in 2023 compared to the previous year. The purpose of this study is to analyze the collaboration process and identify the factors inhibiting the implementation of collaborative governance to eradicate the circulation of illicit cigarettes in Bali Province. This research uses a descriptive qualitative method with a case study approach. Data analysis techniques were carried out by data reduction, data presentation and drawing conclusions from the results of interviews. The results showed that the collaborative process of eradicating illicit cigarettes in Bali Province was quite successful in the exchange of information, the process of coordination, communication, transparency information exchange, mutual trust and understanding of the objectives of the illicit cigarette eradication program have been strongly established. However, there are obstacles in the collaboration process consisting of unclear SOPs, lack of human resources and mismatches in employee competencies in the implementation of collaboration. This study recommends that Customs and Satpol PP develop SOPs, increase the quantity and quality of human resources.